Sistem Kelembagaan Keuangan Bebas Bunga Alternatif bagi Perekonomian yang Berkeadilan: Tinjauan Konstruktif - Jeni Susyanti (Universitas Islam Raden Rahmat, 2019)
The Islamic economic system can be an option during the current world economic system with its market mechanism that can no longer be controlled by anyone and any system. The Islamic economic system is present as an alternative to the alignment of the economic system in a market order that is just and beneficial for human welfare. Islamic sharia principles in asset management emphasize the balance between individual and community interests, where assets must be used for productive things, especially investment activities which are the basis of economic activity in society. Interest-free financial institutions (Islamic financial institutions) as the implementation of the Islamic economic system include two institutions, namely bank financial institutions and non-bank financial institutions. In carrying out their financial activities, the two types of institutions carry out the main principles in transactions, namely: the prohibition of usury (interest) in various forms of transactions, conducting business, and trading activities based on obtaining legal profits according to sharia, and giving zakat. So that the financial institution must have a financial management strategy, properly and following muamalah fiqh.